The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/18479804221132965
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of microbial fuel cells through assembling anodes modified with nanoscale materials

Abstract: In microbial fuel cell (MFC), the anode is the carrier of microbial attachment and growth, and its material and surface structure play a vital role in MFC electricity generation. Therefore, anode surface optimization is an effective way to improve MFC performance. Although the power generation of bacteria has been confirmed and studied as early as the beginning of the 20th century, up to now, MFC still has the extremely challenging problem of low current and low power output in practical application. To improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…In electron transfer via nanowires, Geobacter genera and, very recently, Shewanella have demonstrated their abilities to use their conductive appendages in an electron transfer mechanism outside the cell [66][67][68]. These microbial structures involve cellular outgrowth, known as nanowires, with reported conductivity that is much higher than that of synthetic metallic nanostructures [69,70].…”
Section: Electron Transfer Reactionmentioning
confidence: 99%
“…In electron transfer via nanowires, Geobacter genera and, very recently, Shewanella have demonstrated their abilities to use their conductive appendages in an electron transfer mechanism outside the cell [66][67][68]. These microbial structures involve cellular outgrowth, known as nanowires, with reported conductivity that is much higher than that of synthetic metallic nanostructures [69,70].…”
Section: Electron Transfer Reactionmentioning
confidence: 99%
“…A large number of anode materials have been tested in MFCs, but all of them have some obstacles that make MFC unsuitable for commercial applications [35,36]. The literature has shown that modifying the anode to achieve a large surface area, efficient electron transferability, and bacterial adhesion has become a new research interest in the field of MFCs [37]. The second decisive factor for the power density of the pMFC is the cultivation efficiency of microalgae in the cathode chamber.…”
Section: Power Generationmentioning
confidence: 99%
“…These results were higher than those reported in the above-discussed studies. This achievement in the SC-MFCs was due to the anode electrode modification [49,50]. The reader is referred to a previous overview for a comprehensive review of this topic [51].…”
Section: Designs Configurations and Operationmentioning
confidence: 99%